PERANAN SASTRA DAN BAHASA MELAYU DALAM MEMBANGUN KARAKTER BANGSA - Chairil Effendy (Badan Pengembangan dan Pembinaan Bahasa, 2014)
Literature and language play important role in forming the character of a country. Language that is delicate, neatly arranged, and expressed with good manner in various occasions creates lovely, beautiful, well-mannered, civilized impressions either for the speaker or the listener. Therefore in a long time, whether when it is in the position as lingua franca for the Nusantara people or when it is in the position as regional language, Malay, and Malay literature, has played important role in forming Malay country’s character. Speaking and doing literature using Malay that is based on the ethical and aesthetic values not only colour the life of the noblemen in the kingdom palace, but also among the people. The delivery of certain messages orally through pantun or literary texts such as poem and gurindam that contain a lot of moral values, really contributes to the forming of Nusantara people’s personality and character. The problem is that country’s character is not the destiny or fate, not something that has been available on its own; it is a “course” or “duty”. It must be planted, internalized, built, formed, and kept ground inside the country’s children selves. In this context, language plays important role. Language is the symbolic system that with it men can form, raise, and develop their culture. In relation to it, the position and function of Indonesian and regional (Malay) languages must be reinforced: “schools oblige to develop Indonesian and regional languages to become the part of country’s character building.”AbstrakSastra dan bahasa memainkan peranan penting dalam membentuk karakter suatu bangsa. Bahasa yang halus, tertata rapi, dan disampaikan dengan tatakrama yang baik dalam berbagai kesempatan menimbulkan kesan elok, indah, santun, terhormat, beradab, baik bagi pembicara maupun pendengarnya. Demikianlah dalam waktu yang lama, baik tatkala berkedudukan sebagai lingua franca bagi masyarakat Nusantara maupun ketika berkedudukan sebagai bahasa daerah, bahasa Melayu, pun sastra Melayu, telah memainkan peran penting dalam membentuk karakter bangsa Melayu. Berbahasa dan bersastra dengan bahasa Melayu yang berlandaskan pada nilai-nilai etika dan estetika itu tidak hanya mewarnai kehidupan para bangsawan di istana kerajaan, melainkan juga di tengah rakyat jelata. Penyampaian pesan-pesan tertentu secara lisan melalui pantun atau melalui teks sastra seperti syair dan gurindam yang banyak mengandung nilai-nilai moral, sangat kontributif bagi pembentukan kepribadian dan karakter masyarakat Nusantara. Masalahnya adalah karakter bangsa itu bukanlah nasib bukan pula takdir, bukan sesuatu yang telah tersedia dengan sendirinya; ia adalah “ikhtiar” atau “tugas”. Ia harus ditanamkan, diinternalisasikan, dibangun, dibentuk, dan terus diasah di dalam diri anak-anak bangsa. Dalam konteks ini bahasa memainkan peranan penting. Bahasa adalah sistem simbol yang dengannya manusia dapat membentuk, memelihara, dan mengembangkan kebudayaannya. Berkaitan dengan hal tersebut, kedudukan dan fungsi bahasa Indonesia dan daerah (Melayu) harus diperkuat: “sekolah-sekolah wajib mengembangkan bahasa Indonesia dan bahasa daerah menjadi bagian dari pembangunan karakter bangsa.”